Physiochemical and Sensorial Properties of Burgers Produced from Nubian Goat Meat and Beef - Adam , Yasir Salah Ibrahim (Journal of Food Sciences, 2022)
Purpose: This study was aimed to evaluate sausage processed from different levels of goat meat replacement beef meat. Methodology: Beef top side cut and goat leg were purchased from local market and used according to A ( Beef 50 % ,goat meat 50 % ) , B( beef 25 % , goat meat 75 % ) , C ( goat meat 100 % ) and D ( Beef 100 % ) as control group, and to compare the goat meat sausages with the most common commercial sausages made with beef. Findings: The chemically, crude protein percentage was significantly different (p<0.05) in sausage treatments where higher in beef sausage, ash, and fat were also different increased with beef meat among sausage treatments, on the other hand moisture content increased with goat meat. Ultimate pH and cooking loss % of sausage treatments were significantly different (p <0.05). Total viable bacterial counts of sausage treatments were determined. Sensory attributes, including color, flavor, juiciness, tenderness, and overall acceptability among the different types of sausages prepared were no significantly differences (p > 0.05) Unique contribution to theory, practice and policy: Goat meat mainly from animals out of quality brands with low commercial value can be valorized when processed, giving the opportunity to increase its consumption and acceptability. In this study goat meat incorporated to the sausage ingredients with beef fat to evaluated the quality and flavor of sausage replacing beef meat. Sudanese Nubian goat meat useful for use in meat processing products with good characteristics and more acceptable for the final products. More researches for use goat meat in other meat products.